2022
DOI: 10.2471/blt.21.287654
|View full text |Cite
|
Sign up to set email alerts
|

Infodemics and health misinformation: a systematic review of reviews

Abstract: Objective To compare and summarize the literature regarding infodemics and health misinformation, and to identify challenges and opportunities for addressing the issues of infodemics. Methods We searched MEDLINE®, Embase®, Cochrane Library of Systematic Reviews, Scopus and Epistemonikos on 6 May 2022 for systematic reviews analysing infodemics, misinformation, disinformation and fake news related to health. We grouped studies based on similarity and retrieved evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(110 citation statements)
references
References 50 publications
3
106
0
1
Order By: Relevance
“…held more misinformed views across all 25 statements ( Figure 2 ). Aside from these sources being commonly held responsible for spreading misinformation and for amplified misinformation vulnerability [ 1 , 15 , 136 , 137 , 138 , 139 , 140 , 141 ], personal factors such as lower levels of health literacy cannot be discounted [ 142 , 143 ]. Research has indicated that individuals with health literacy deficiencies are more prone to use non-scientific sources such as television, social media, blogs, or celebrity webpages [ 144 , 145 ] and more susceptible to health misinformation [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…held more misinformed views across all 25 statements ( Figure 2 ). Aside from these sources being commonly held responsible for spreading misinformation and for amplified misinformation vulnerability [ 1 , 15 , 136 , 137 , 138 , 139 , 140 , 141 ], personal factors such as lower levels of health literacy cannot be discounted [ 142 , 143 ]. Research has indicated that individuals with health literacy deficiencies are more prone to use non-scientific sources such as television, social media, blogs, or celebrity webpages [ 144 , 145 ] and more susceptible to health misinformation [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the source used for dietary change contains more hazardous, unsafe, or riskier misinformation, then there is a higher risk of health harm [ 146 ]. This underscores the need for educational and communication initiatives to counter misinformation and disinformation exposure and impact, through such approaches as targeted warnings, awareness campaigns, and correction strategies, alongside policy-, technological-, and regulatory-level interventions [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, for anti-criminalization supporters, creating policies controlling health misinformation and disinformation goes against freedom of speech and a free flow of information. Countermeasures that would suit both points of view can be awareness campaigns for patients and health-care professionals, the creation and dissemination of easy-to-navigate platforms with evidencebased data, the improvement of health-related content in the mass media by using high-quality scientific evidence, the increase of high-quality online health information and improved of media literacy [43].…”
Section: Infodemic Managementmentioning
confidence: 99%